2009
DOI: 10.1515/jpem.2009.22.6.547
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Disorders of Neonates Born to Mothers with Graves' Disease

Abstract: Maternal hyperthyroidism implies the risk of thyroid abnormalities in the newborn. We describe retrospectively the clinical presentation, treatment and follow up of 28 children born of hyperthyroid mothers. Patients were subdivided as follows: Group A (neonatal hyperthyroidism) (n=9): born from eight hyperthyroid mothers and one thyroidectomized mother. Children born from untreated mothers consulted between 1 and 7 days of life, while those born from treated mothers consulted between 8 and 17 days. Eight neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 22 publications
3
29
0
3
Order By: Relevance
“…Low birth weight (odds ratio (OR)Z9.2, 95% confidence interval (CI) 5.5-16), prematurity (ORZ16.5, 95% CI 2.1-130), eclampsia (ORZ4.7, 95% CI 1.1-19.7), and risk of miscarriage are more common in untreated hyperthyroid mother than in those who are euthyroid (9,14,15). The frequency of small-forgestational age infants may increase in those who remain hyperthyroid (26.7 vs 7.7%) compared with those who were euthyroid throughout pregnancy (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low birth weight (odds ratio (OR)Z9.2, 95% confidence interval (CI) 5.5-16), prematurity (ORZ16.5, 95% CI 2.1-130), eclampsia (ORZ4.7, 95% CI 1.1-19.7), and risk of miscarriage are more common in untreated hyperthyroid mother than in those who are euthyroid (9,14,15). The frequency of small-forgestational age infants may increase in those who remain hyperthyroid (26.7 vs 7.7%) compared with those who were euthyroid throughout pregnancy (16).…”
Section: Resultsmentioning
confidence: 99%
“…Overt hyperthyroidism has well-documented adverse impacts on pregnancy outcomes (8)(9)(10). Therefore, despite its rarity, recognition and proper management of hyperthyroidism during pregnancy is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of Graves' disease in pregnant women is estimated to be 0.2%. Only 1-2% of infants born to these pregnant women present with fetal and neonatal hyperthyroidism [3,4]. Transplacental transfer of maternal TSHR-Ab (Thyroid Stimulating Hormone Receptor Antibody) plays an important role in occurrence of neonatal Graves disease.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical signs and symptoms may be delayed up to 7-10 days because of antithyroid drugs or TSHR blocking antibodies found in the serum (26). In another study, it was observed that the clinical picture appeared in the postnatal 1 st -3 rd days in babies of mothers who were not using medication, and in the postnatal 7 th -17 th days in the other babies (27). The clinical picture may not always be prominent.…”
Section: Clinical Picturementioning
confidence: 99%
“…Subsequently, the level in the fetus gradually increases and exceeds the mother's level in the term newborn (14). Although it has been proposed that the clinical picture may start from the 21 st week when the antibody level increases and the fetal TSH receptors become responsive, the picture of fetal hyperthyroidism generally becomes prominent in the [26][27][28] th weeks (5). Both sexes are affected equally.…”
Section: Treatment Approachesmentioning
confidence: 99%